Victims of Cyber Crimes in Indonesia: A Criminology and Victimology Perspective (Universitas Negeri Semarang, 2022)
Crimes that occur in cyberspace are born as a result of the negative impact of technological developments, crimes that occur in various forms and types have consequences for the legal protection of users, this is important considering that every human being must be protected in accordance with his dignity as a human being. One form of state responsibility for the protection of its citizens is to provide legal guarantees and concrete actions that protect the community from all forms of crime or other deviant acts that may be experienced by the community, both in the real world and in cyberspace. Crimes that occur in cyberspace or commonly referred to as cybercrime. This study is aims to analyze and examine the victims of cyber crime in the perspective of criminology and victimology. Criminology approach used to answer the motive, factors, and response of the crime, and victimology approach to understand more comprehensively concerning to the victim’s protection and the role of the victims in the cybercrime.